(untitled) (Swiss Medical Weekly, 2026)
BACKGROUND: Urban swimming, especially in the Aare River, is popular in Switzerland but carries risks, particularly for those unfamiliar with its currents and hazards. This study describes the epidemiology of river-related emergency department (ED) visits, focusing on injury patterns, patient demographics and presentation characteristics. METHODS: A retrospective cross-sectional study at the University Hospital of Bern was conducted, analysing river-related ED visits from 2012 to 2024. Data on demographics, injury types, triage levels and outcomes were extracted from electronic medical records. RESULTS: A total of 263 river-related ED visits were identified among a total of 541,561 ED visits over the study period (proportional incidence: 0.49 per 1000 ED consultations, 95% CI: 0.43–0.55). Most patients were male (62.7%), aged ≤35 years (65.4%) and Swiss nationals (65.4%). The most frequent injuries were trauma (63.1%), mainly affecting the lower extremities (30.8%) and head/face (16.3%), often due to collisions with submerged objects or bridge jumping. Drowning cases (12.2%) were less common, with seven fatalities (2.7%). Most incidents occurred in the summer between June and August (78.7%), with 37.3% on weekends. Suicide attempts (20.4% vs 3%) and boating-related incidents (11.2% vs 6.7%) were more common in females and jumping-related incidents more frequent in males (22.4% vs 11.2%), p <0.001. Hypothermia was significantly more often found in non-Swiss nationality ED visits (p = 0.002) and those of people aged >35 years (p <0.001). Compared to younger patients, those aged >35 years were significantly more likely to be triaged as life-threatening (22% vs 7.6%; p <0.001), report intentions other than swimming (notably more suicide attempts and accidents; p <0.001), and had higher rates of admission to an ICU or of transfer to a psychiatric clinic (p <0.001). CONCLUSION: River-related ED visits are a recurring seasonal concern, primarily affecting young males. People with non-Swiss nationality and those engaging in high-risk activities are at higher risk. Adopting a multilingual approach could be a key objective of safety campaigns to more effectively reduce risks for non-Swiss swimmers and promote safer swimming practices in urban waters. Prevention efforts should continue to focus on public education, enhanced safety signage and improved emergency preparedness.